Analisis Komparatif Pengaruh Faktor Lingkungan Abiotik dan Biotik terhadap Diversitas Flora Normal Ayam : Sebuah Tinjauan Sistematis - Lestari Lestari; Rizki Amelia Nasution (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The normal flora of chickens refers to the microbial communities that naturally inhabit the gastrointestinal tract and body surfaces of chickens, playing a crucial role in health, digestion, and immunity. This community consists of beneficial bacteria such as Lactobacillus, Bifidobacterium, and Bacillus, which assist in feed fermentation, vitamin synthesis, and inhibition of pathogenic growth. Additionally, the normal flora may include potential pathogenic bacteria such as Escherichia coli, Salmonella spp., and Campylobacter, which can cause diseases if microbial balance is disrupted. The diversity and balance of the microbiota are influenced by various abiotic factors, including feed quality, access to clean water, ambient temperature, humidity, and environmental hygiene. Biotic factors, such as microbial interactions, rearing systems, and contact with other animals, also play a significant role in determining microbial composition. Several studies have shown that the use of feed additives, such as probiotics and phytogenics, can enhance populations of beneficial bacteria while suppressing pathogenic bacteria. Extensive rearing systems, which provide chickens with more space and exposure to natural environments, tend to increase microbiota diversity compared to semi-intensive systems with more restricted conditions. Understanding these factors is essential for developing effective health management strategies and optimizing safe and sustainable poultry production.